A comunicação casa escola no contexto da inclusão de pessoas com TEA - Almeida, Tânia Santana de (2016)
The workinvestigateshow communication occursbetweenschoolandfamily in thecontextofTEA .Thuswepresent a briefreviewoftheliteratureonschoolenrollmentrates ,especiallythehistoricalaspects as well as ontheautismspectrumdisorder . In thiscontext ,ishighlightedfamilyandtheirpresencecontinuously for thedevelopmentofthepersonwith ASD in school , giventhattheformsof communication thatcanbeusedbythefamilyofthepersonwith ASD andtheschool are highlighted . The literatureaddressestheissueofinclusionofstudentswithASD ,butlittlehasbeeninvestigatedaboutrelationshipsandformsof communication betweenschoolandfamily , eveniftheofficialdocumentsonschoolinclusionexpresstheimportanceofthefamily 's presence in theschool. Thisisstudy design ofmultiple cases involvingthreemothersofstudentswithautism in kindergartenandfirst grades of municipal schools in Santa Maria- RS andtheirteachers. The resultsshowedthatthe ideal typeof communication consideredbytheschoolisdonethroughtheagenda ,butthemothersconsiderinsufficientthisformof communication . Involveparents in activitiesandschoolroutineis a communication strategyusedtoalsomaintain a dialogue withfamilyparticipates ,however , accordingtotheteachers , thecontents are alwaysacademicnature . Finally , communication between home-school in thecontextoftheperson'sinclusionwith ASD showedinefficiently .